ReSAKSS Regional Strategic Analysis and Knowledge Support System - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The most recent update of the brochure is dated 2018. This replaces versions published in 2016, 2014, and 2013. The 2018 and 2013 versions were translated to French.